ADAPTATION OF UKRAINIAN LEGISLATION IN THE PART OF TAXATION, ACCOUNTING AND AUDITING TO THE REQUIREMENTS OF THE EUROPEAN UNION - Puhachenko, Olha; Fomina, Tatiana (SWorld-Ger Conference proceedings, 2023)
This study explores the intricacies of the adaptation of Ukrainian legislation concerning taxation, accounting, and auditing to comply with the requirements of the European Union. The analysis encompasses provisions outlined in the "Law of Ukraine on the